Benign Synthesis of Black Microspheres of Anatase TiO2 with Paramagnetic Oxygen Vacancies through NH3 Treatment. Issue 56 (8th September 2017) - Maqbool, Qysar; Srivastava, Aasheesh
Abstract: Coloured TiO2 is coveted for its ability to extract energy from the visible region of electromagnetic spectrum. Here a facile synthesis of black anatase titania microspheres (B‐TiO2 ) through a two‐step process is reported. In the first step, amorphous white TiO2 microspheres (W‐TiO2 ) are obtained by hydrolysing titanium tetraisopropoxide by ammonia vapours in ethanol. In the second step, theW‐TiO2 is thermally annealed at 500 °C to obtainB‐TiO2 . The diffuse reflectance analysis showed thatB‐TiO2 absorbs across visible spectrum with absorption extending well into NIR region. Raman scattering together with EPR analysis showed compelling evidence of the existence of oxygen deficiency within the crystal inB‐TiO2 that induces black colouration in the sample. The defects present in the black anatase sample were confirmed to be single‐electron‐trapped (or paramagnetic) oxygen vacancies (Vo ⋅ ) by XPS and EPR studies. The magnetic susceptibility studies showed existence of antiferromagnetic interactions between these unpaired electron spins. Abstract : Black ball : A facile, two‐step synthesis of phase‐pure black anatase microspheres (B‐TiO2 ) with paramagnetic oxygen vacancies is reported.